Challenges to Iran's role in Iraq in the post-Soleimani era: Complex rivalries, fragmented alliances, declining soft power - Hamidreza Azizi (Stiftung Wissenschaft und Politik (SWP), 2021)
On January 3, 2020, the Iranian Quds Force commander, Maj. Gen. Qassem Soleimani, was assassinated by the United States in Iraq. He was considered the mastermind behind Iran's regional strategy, especially in Syria and Iraq. A year and a half later, the Islamic Republic continues to wield considerable influence in Iraq, and Iran-backed militias continue to violently pressure US forces to leave Iraq. However, Iran now faces a series of serious challenges that are directly and indirectly related to Soleimani's death. In the geopolitical and economic spheres, the influence of Iran's rivals in Iraq has increased, while Tehran's room for maneuver has become increasingly limited. In the political arena, divisions among Iran-backed forces in Iraq have increased, while Iran's direct influence over the Iraqi government has been declining. At the same time, rising anti-Iranian sentiments among the Iraqi people have reduced Iran's social capital in the neighboring country. The combination of these factors seems to be limiting Iran's influence in Iraq. The EU should build upon this opportunity to support a strong Iraqi government that pursues a multi-vector foreign policy.
Keywords: 320